2011
DOI: 10.1590/s0100-06832011000300027
|View full text |Cite
|
Sign up to set email alerts
|

Produção de girassol sob estresse salino e adubação nitrogenada

Abstract: RESUMOA limitada disponibilidade de águas de baixa salinidade na região semiárida brasileira faz com que os produtores utilizem, na irrigação, águas com teores salinos de moderado a alto. Considerando que o girassol (Helianthus annuus L.) vem ganhando destaque nessa região por se caracterizar como fonte potencial de energia renovável, realizou-se esta pesquisa visando avaliar a sua produção sob diferentes níveis de salinidade da água de irrigação (CEa) e doses de adubação nitrogenada, em experimento conduzido … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
18

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 25 publications
3
29
1
18
Order By: Relevance
“…Excess of salts in water, independently of their cationic nature, cause damage to various physiological and biochemical processes such as respiration, photosynthesis, protein synthesis and lipid metabolism, and may also lead the plant to a state of water stress with loss of water to the external environment and to suffer from toxicity, which will result in serious damage to the growth and production of plants (Esteves& Suzuki, 2008). Corroborating with the results obtained Nobre et al (2011) found that the effect of irrigation with water of different saline levels and nitrogen rates on sunflower growth and flowering, decreased both internal and external diameterof capitulum. According to Figure2B, the phytomass of the capitulum with achenes (PCA) of the plants differed significantly due to the use of water with different cationic nature, and the highest value (88.03 g) was obtained using water of the treatment S 1 (control).…”
Section: According Tosupporting
confidence: 61%
See 3 more Smart Citations
“…Excess of salts in water, independently of their cationic nature, cause damage to various physiological and biochemical processes such as respiration, photosynthesis, protein synthesis and lipid metabolism, and may also lead the plant to a state of water stress with loss of water to the external environment and to suffer from toxicity, which will result in serious damage to the growth and production of plants (Esteves& Suzuki, 2008). Corroborating with the results obtained Nobre et al (2011) found that the effect of irrigation with water of different saline levels and nitrogen rates on sunflower growth and flowering, decreased both internal and external diameterof capitulum. According to Figure2B, the phytomass of the capitulum with achenes (PCA) of the plants differed significantly due to the use of water with different cationic nature, and the highest value (88.03 g) was obtained using water of the treatment S 1 (control).…”
Section: According Tosupporting
confidence: 61%
“…For the factor N doses (ND), there was no significant influence for any of the studied variables, while the interaction (S x ND) showed to significance only for the dry phytomass of the capitulum (DPC). Nobre et al (2011) evaluating the production of sunflower cv. Embrapa 122 / V-2000 cultivated under different irrigation water salinity levels (ECw: 0.5 to 4.9 dS m -1 , prepared with addition of NaCl) and nitrogen fertilization rates, also observed no interaction between these factors for any production variable evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the application of ammonium (NH 4 + ) can contribute to a higher absorption of anions and, in salt-affected soils with high amounts of chlorides, NH 4 + will be absorbed preferentially, causing lower damages to plants. Preliminary results have been observed in experiments with castor bean (SOARES et al, 2013;LIMA et al, 2014) and sunflower (NOBRE et al, 2011;NOBRE et al, 2014).…”
Section: Introductionmentioning
confidence: 86%